Tacrolimus inhibits angiogenesis and induces disaggregation of endothelial cells in spheroids – Toxicity testing in a 3D cell culture approach. (December 2018) - Thoms, Stefanie; Ali, Alaa Ibrahim; Jonczyk, Rebecca; Scheper, Thomas; Blume, Cornelia
Abstract: The administration of immunosuppressive drugs is a necessary therapeutic measure in organ transplantation to prevent rejections. However, the use of temporarily high dosed immunosuppressive drugs is associated with cytotoxicity and adverse side effects that could induce endothelial dysfunction. The aim of this work is to evaluate the effect of the administrated drugs tacrolimus and mycophenolic acid (MPA) on human umbilical vein endothelial cells (HUVECs). Whereas MPA showed no significant toxicity in a dose-dependent manner, a dose-response curve of tacrolimus treatment could be obtained in 2D monolayer. Due to limited cell-cell and cell-extracellular matrix (ECM) interactions in 2D monolayers, 3D spheroids have been established. The comparison of IC50 values demonstrated that tacrolimus is more toxic towards endothelial cells in 3D spheroids (IC50 value = 27.19 μg/ml) than in 2D monolayers (IC50 value = 40.23 μg/ml). Moreover, the maximal trough level of tacrolimus achieved in immunosuppressive therapy (18 ng/ml) resulted in low disaggregation of the spheroids and decreased vessel areas with increased number of end points of tubular-like structures in the angiogenesis assay even if no toxic effect could be detected. Thus, our approach unseals very sensitive cytotoxic effects of tacrolimus on the vasculature in organ recipients after immunosuppressive therapy. Highlights: Dose-dependent toxicity of tacrolimus towards immature endothelial cells High value of a 3D cell culture model to evaluate sensitive toxic effects of tacrolimus Tacrolimus trough level during therapy trigger disaggregation of spheroids without affecting cell viability. Tacrolimus inhibits tubular-like structure formation of HUVECs as a model for angiogenesis.